Holocene-aged human footprints from the Cuatrocienegas Basin, NE Mexico - Felstead, Nicholas J.; Gonzalez, Silvia; Huddart, David; Noble, Stephen R.; Hoffmann, Dirk L.; Metcalfe, Sarah E.; Leng, Melanie J.; Albert, Bruce M.; Pike, Alistair W.G.; Gonzalez-Gonzalez, Arturo; Jimenez-Lopez, Jose Concepcion (Elsevier, 2014)
Two sets of well-preserved human footprints have been found in tufa sediments in the Cuatrociénegas Basin, NE Mexico, and here we present their U-series dates of 10.55 0.03 ka and 7.24 0.13 ka. The former are the oldest known footprints in Mexico, although their exact location is unknown, the latter form part of a trackway with eleven in situ human footprints. Oxygen (and to a lesser extent) carbon isotope data from the sediments suggest that the tufa with in situ footprints formed during a transition to a wetter (less arid) period, while pollen evidence indicates the basin floor presence of pecan (Carya) and willow (Salix sp.) before the onset of regional Chihuahuan Desert aridity. These footprints confirm the presence of humans, possibly nomadic hunteregatherer groups, which persisted until the 18th Century AD.